Factors Related to Covid-19 Prevention Behaviour on Market Traders in Pontianak - Sukemi, Maria Yolan; Trisnawati, Elly; Selviana, Selviana (Jurnal EduHealth, 2022)
Informal sector workers are one of the workgroups that are vulnerable to contracting Covid-19, because they interact more directly with many people, so they can increase the risk of spreading a disease. The report by the Satuan Tugas Penanganan COVID-19 as of May 8 2022 shows that the cumulative number of people who are reprimanded related to 3M based on the location of the crowd is occupied by "Market" in first place. The purpose of this study was to determine the factors associated with Covid-19 prevention behavior in market traders in Pontianak. This research is an analytic observational study with a cross sectional approach. The total sample is 97 respondents taken by purposive sampling. The research instrument used a questionnaire and the data were analyzed using the Chi-Square test. Results: There is a significant relationship between knowledge (p = 0.000), attitude (p = 0.000), availability of hand washing facilities (p = 0.013), social support (p = 0.000), and availability of educational media (p = 0.027) with behavior prevention of Covid-19, and there is no relationship between vaccination status (p = 0.071) and behavior of Covid-19 prevention in market traders in Pontianak. Conclusion: there is a significant relationship between knowledge, attitude, availability of hand washing facilities, social support, and availability of educational media with Covid-19 prevention behavior among market traders in Pontianak.